The Nibelungenlied Today Its Substance, Essence, and Significance - Mueller, Werner A. (Werner Achilles), 1903-1999 (University of North Carolina studies in the Germanic languages and literatures ;, 2020)
This thorough study of the moral values of the Nibelungen and of their paradoxical behavior posits the work as an indictment of a society that results time and again in collective human tragedy. Told with tragic insight, yet sympathetically, the epic may well be described as the story of man, the victim of himself. Mueller analyzes the work in three chapters, focused on substance, essence and significance, in order to make the epic poem relevant to a modern audience.